1999
DOI: 10.1002/(sici)1097-4652(199912)181:3<433::aid-jcp7>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Noninsulin‐dependent diabetes mellitus occurs in mice ectopically expressing the human Axl tyrosine kinase receptor

Abstract: The axl tyrosine kinase receptor is aberrantly expressed on myeloid cells of many individuals afflicted with chronic myelogenous leukemia (CML) and other myeloid leukemias. Although previous studies demonstrated this kinase to have oncogenic potential, it is not known whether axl actively participates in the onset and/or progression of CML. We addressed this question by generating transgenic mice possessing constitutive ectopic expression of human axl throughout cells of the myeloid hematopoietic lineage throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
0
13
1
1
Order By: Relevance
“…In 1995, Shugart et al (21) found that Gas6 plays a pivotal role in enhancing 3T3-L1 adipocyte proliferation. Augustine et al (25) accidentally found that transgenic mice with overexpression of Gas6/TAM signaling exhibit progressive obesity. Moreover, adipose tissue is highly vascularized, and its growth depends on vascularization (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1995, Shugart et al (21) found that Gas6 plays a pivotal role in enhancing 3T3-L1 adipocyte proliferation. Augustine et al (25) accidentally found that transgenic mice with overexpression of Gas6/TAM signaling exhibit progressive obesity. Moreover, adipose tissue is highly vascularized, and its growth depends on vascularization (38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies of transgenic mice found that Gas6/ TAM signaling might recruit macrophages from the bone marrow into the adipose tissue, implying that Gas6/TAM signaling may play a potential role in the pathogenesis of adipose tissue inflammation (14,23,24). Interestingly, transgenic animals that ectopically express the TAM family of receptors also develop progressive obesity with elevated circulating TNF-␣ concentrations and severe systemic insulin resistance (25). This preclinical evidence indicates that the Gas6/TAM system likely represents an important pathogenic mechanism for obesity and obesityassociated inflammation and insulin resistance.…”
mentioning
confidence: 99%
“…A recent study reported an association between high plasma GAS6 concentrations and a decreased risk of developing of type 2 diabetes mellitus [24]. Additionally, a transgenic mouse strain possessing a constitutive active AXL receptor throughout cells of the myeloid haematopoietic linage, showed a non-insulin dependent diabetes mellitus phenotype with gradual age-dependent reduction in the number of insulin-positive cells, possibly due to sequestering of free GAS6-ligand present in plasma [25]. However, the possible role of GAS6 in regulation of beta cell mass or whether any receptors for GAS6 are present in beta cells has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic mice ectopically expressing AXL in myeloid cells, were observed to develop phenotypes similar to noninsulin-dependent diabetes mellitus. 39 These animals displayed hyperglycemia, severe insulin resistance, hyperinsulinemia, hepatic lipids and pancreatic islet dysplasia, progressive obesity, but did not exhibit hyperphagia.…”
Section: Discussionmentioning
confidence: 96%